Halide Perovskite, a Potential Scintillator for X‐Ray Detection. Issue 10 (2nd September 2020) - Zhou, Faguang; Li, Zhizai; Lan, Wei; Wang, Qian; Ding, Liming; Jin, Zhiwen
Abstract: Scintillator is a unique class of luminescent materials, which is extensively used in many fields such as nondestructive testing, medical imaging, space probes, etc. Compared with the disadvantages of traditional scintillator materials which have high cost, are fragile, have long response time and low spatial resolution disadvantages, metal halide perovskites are considered to be the most potential scintillator materials in X‐ray detection and medical imaging due to their preeminent performance of radiative absorption, carrier transportation, high photoluminescence, high atomic number ( Z ), high‐quality elements, and low‐temperature solution process. However, this material has blemishes such as poor stability and low luminous efficiency in the application of X‐ray detection. In recent years, many start‐of‐art and momentous works have been carried out to solve these problems. Herein, it is intended to summarize the progress of perovskite scintillators to date and propose a scheme for the development of their bottlenecks. First, the physical phenomena and main parameters of scintillators are summarized. Second, the classification of scintillator materials and their application of perovskite scintillators are outlined. Finally, the issues that remain in the application of perovskite scintillators and provide a simple outlook for possible directions in future applications are discussed. Abstract : The perovskite scintillator is recognized as the scintillator material with the most potential for X‐ray detection. This review discusses the scintillator from physical phenomena, key parameters, and material classification system, which mainly introduces the classification and application of perovskite scintillator materials. Finally, a brief outlook is presented, including the issues that remained and the possible direction for further development.